ON-SR UII: AN ONLINE SELF-REGULATED LEARNING WEB APPLICATION TO ASSIST INDEPENDENT COLLEGE LEARNERS - Ahmad R. Pratama; Puji Rahayu; Andri Setiyadi; M. Fachry Azhar; M. Fajri Ashshiddiq (Jurnal Riset Informatika, 2022)
Self-regulated Learning (SRL) is a learning method that strongly emphasizes the importance of self-learning skills. Unfortunately, many existing educational technologies employed by colleges and universities continue to place a premium on technical support for the learning process within the classroom that does not provide the same level of support for SRL. This study aims to close this gap by developing the ON-SR UII, a new SRL platform that can assist college students in their quest to become independent learners. Using the design thinking approach, ON-SR UII is developed as a responsive web app that can be accessed by college students through the Internet anywhere at any time at their own pace using any computing device of varying screen sizes. This article describes how ON-SR UII was designed before its Prototype was developed, deployed, and evaluated by stakeholders for functionality, usability, and responsiveness. The encouraging results indicate that ON-SR UII has the potential to be widely implemented, allowing for the measurement of its implications in future research.